Exploring Opportunities for Engaging Public Health Organizations in Transportation Planning. (July 2015) - Li, Jianling; Casey, Colleen; Brewer, Lou K.
Despite a call for collaboration, there remain challenges to engaging the public health community in the regional transportation planning process. Using an integrated framework of network theory and collaborative planning, we explore collaboration barriers and opportunities between transportation and public health communities. Analysis of primary data collected from a focus group and secondary data from 43 national case studies suggests that major perceived barriers include a lack of formal and informal mechanisms and knowledge management practices that facilitate collaboration. Coordination of policies at multiple levels, leadership, trust, and data sharing are recognized as important tools for collaboration. Implications are discussed.